Perceptions of Students and Teachers in an English Course: Reconstructing a Syllabus (2021)
This initial research report aimed to explore the impact on students’ and teachers’ learning and teaching expectations of an English Course containing English for Specific Purposes (ESP), Saber Pro samples, and the use of graded audiobooks by interpreting students and teachers’ perceptions. Data was gathered through a survey and a focus group interview. The initial findings revealed that the current syllabus was designed efficiently in terms of layout, but certain aspects concerning content, language level, methodology, and evaluation needed to be adjusted. The interpretation of this academic community’s perceptions resulted in the reconstruction of the course syllabus.